2012
DOI: 10.13109/prkk.2012.61.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Erhebung von Suizidgedanken bei Jugendlichen: Vergleich zweier Instrumente

Abstract: Summary Assessment of Suicidal Ideation in Adolescents: Comparison of two InstrumentsStandardized instruments are crucial for a valid assessment of suicidal behavior. In questionnaire assessments the wording of questions can influence the results. In this study we compared the congruence of the Self-Harm Behavior Questionnaire (SHBQ) and the Ottawa Self-Injury Inventory (OSI) as measures of prevalence of suicidal ideation in an adolescent sample (n = 665, mean age: 14.8, SD: 0.66). We found a life-time prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We agree that the choice of instruments is crucial for providing the valid assessment of suicidal ideation and suicide attempts. Published studies have shown high agreement between the existing instruments (Self-Harm Behavior Questionnaire and Ottawa Self-Injury Inventory), which were also used in our study [60]. The method that we used to define migration background differs from that used in other studies, particularly in the US.…”
Section: Discussionmentioning
confidence: 88%
“…We agree that the choice of instruments is crucial for providing the valid assessment of suicidal ideation and suicide attempts. Published studies have shown high agreement between the existing instruments (Self-Harm Behavior Questionnaire and Ottawa Self-Injury Inventory), which were also used in our study [60]. The method that we used to define migration background differs from that used in other studies, particularly in the US.…”
Section: Discussionmentioning
confidence: 88%
“…An important exception was the Self-Injury scale. Results of the test of internal consistency, test-retest reliability, and convergent validity for the Self-Injury subscale provoke questions of this subscale’s performance and suggest the need for further subscale refinement, informed by current research on best assessment practices for this complex phenomenon (Mundt et al, 2010; Plener et al, 2012; Posner et al, 2011). However, Self-Injury displayed the highest sensitivity to average activation scores across the study and the third highest sensitivity to week-to-week fluctuations behind Disinhibition and Mania in the MLM analyses.…”
Section: Discussionmentioning
confidence: 99%